Acquisition of transversal competencies through a project-based learning model for computer systems engineering students - Julieta Noguez; Enedina Ortega Gutiérrez; Luis Neri; Julio E. Rubio (Frontiers in Education)
IntroductionThis article presents an innovative educational practice to promote transversal competences in computer engineering university students, through Project Based Learning (PjBL), providing students with the benefit of experiential learning. Challenges of a social nature were chosen, which are related to demographic aging. Once the course information has been collected, the challenge was to identify whether the students have really acquired the cross-cutting competencies that they should have developed on the course.MethodsAfter applying the model and pedagogical design of the Project-Based Learning (PjBL) methodology, and given the characteristics of the information sources used, a research design was carried out from a qualitative approach through the grounded theory method whose purpose is to induce substantive theory, related to learning, application, and emergence of transversal skills and the pedagogical strategy of the course.ResultsThe cross-cutting competencies identified were collaboration for efficient teamwork, communication among team members, and support and communication with the teacher and were noted to be of great importance for finishing with a high-quality final project.DiscussionUnlike other studies that are based on the evaluation of learning through grades, self-reported questionnaires, rubrics, tests, interviews, observation, self-reflection journals, etc., this research was conducted from a qualitative approach through the grounded theory method. According to the results obtained, it has been possible to identify the most relevant language elements for the studies and thus infer the acquisition of transversal competencies in university students of computer engineering, developed through the PjBL technique, providing students with the benefit of experiential learning.